PERDAGANGAN ETHEREUM DI INDODAX EXCHANGE DALAM PERSFEKTIF SYARIAH - Muhamad Khoirul Umam (Istithmar: Jurnal Studi Ekonomi Syariah, 2019)
In view of Islamic law Ethereum as a digital asset that is traded in cyberspace.The value of cryptocurrency surges and fluctuates, it is influenced by buying and selling demand. Indodax exchange is an official digital asset site in Indonesia that trades more than 40 digital currencies.The purpose of this study is to analyze whether cryptocurrency is worthy of value as money having a certain value, and also seen from the Indonesian government through Bank Indonesia has issued regulation No. 16/8/PBI/2014, which explicitly prohibits the use of bitcoin, Ethereum and altcoin for use in financial transactions in cash. So that raises research questions how the cryptocurrency law in the form of coin ethereum in Islamic law. The results of this study explain ethereum has advantages and disadvantages. Among its advantages is that users can use exchanges or transactions without a third service (bank), and can be traded at merchandise stores.However, ethereum losses are more frequent, such as fluctuating values each time, not listed as commodities, not watched by the Financial Services Authority (OJK), they present elements of gharar (uncertainty) and maysir (gambling) or (betting), which are used for money laundering and purchase of illegal drugs.